2021
DOI: 10.3390/jcm10081790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Primary Repair for Perforated Peptic Ulcer: 10-Year Experience in a Single Center

Abstract: Background: Perforated peptic ulcer (PPU) is a disease whose incidence is decreasing. However, PPU still requires emergency surgery. The aim of this study was to review the clinical characteristics of patients who received primary repair for PPU and identify the predisposing factors associated with severe complications. Method: From January 2011 to December 2020, a total of 75 patients underwent primary repair for PPU in our hospital. We reviewed the patients’ data, including general characteristics and periop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(14 reference statements)
0
2
0
2
Order By: Relevance
“…Therefore, immediate appendectomy is the preferred treatment option for suspected acute appendicitis in pregnancy [25]. In 2007, Yilmaz et al demonstrated that the time interval from the onset of symptoms to surgery (whether laparoscopy or laparotomy) should not exceed 20 hours to ensure optimal maternal and fetal well-being [26]. The laparoscopic technique for acute appendicitis in pregnancy offers several key advantages over open laparotomy, including the use of milder anesthetics, which reduces the risk of fetal distress, shorter hospitalization time, reduced postoperative pain, a better intraoperative field of view, faster recovery of gastrointestinal function, and quicker patient mobilization [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, immediate appendectomy is the preferred treatment option for suspected acute appendicitis in pregnancy [25]. In 2007, Yilmaz et al demonstrated that the time interval from the onset of symptoms to surgery (whether laparoscopy or laparotomy) should not exceed 20 hours to ensure optimal maternal and fetal well-being [26]. The laparoscopic technique for acute appendicitis in pregnancy offers several key advantages over open laparotomy, including the use of milder anesthetics, which reduces the risk of fetal distress, shorter hospitalization time, reduced postoperative pain, a better intraoperative field of view, faster recovery of gastrointestinal function, and quicker patient mobilization [27].…”
Section: Discussionmentioning
confidence: 99%
“…Wound infections occurred in 6.2% of cases, chest infections in 3.6%, intra-abdominal abscesses in 4.1%, and postoperative leaks in 3.6% of cases 15 .In another study from Pakistan's Quetta Following duodenal ulcer perforation, organ space infections developed in 16(6.13%) individuals and sepsis in 10 (3.83%) 16 . The most frequent complications following peptic ulcer repair, according to a study from Korea, were leakage or fistula (5/75, 6.7%), followed by an infected wound (4/75, 5.3%) 17 . While in our study surgical site infection were most frequently noted in patients operated in emergency with (p=0.418).…”
Section: Discussionmentioning
confidence: 99%
“…La úlcera gástrica o duodenal perforada es una urgencia quirúrgica asociada a mortalidad a corto plazo cercana al 30%, por lo que requiere diagnóstico y tratamiento quirúrgico precoz (6) . La úlcera duodenal perforada durante el embarazo o el puerperio es relativamente rara, ya que el embarazo disminuye los síntomas de la enfermedad ulcerosa péptica y la tasa de complicaciones parece disminuir en forma significativa (2) .…”
Section: Discussionunclassified